Effect of Spice Concentration and Storage Time on the Quality of Instant Cassava Leaf - Rudi Ardiansyah; Terip Karo-Karo; Lasma Nora Limbong (Universitas Sumatera Utara, 2014)
Along with the increasing demand for vegetables and to increase their sale value, until needed right preparation. The addition of flavor seasoning and drying form the treatment methods that can increase the shelf life of the material. This study was conducted to determine the spice concentration and storage time to produced the manufacture of instant cassava leaf. This study used a completely randomized design with two factors. The parameters analyzed were moisture content, fiber content, fat content, ash content and organoleptic values (color, smell, taste and appearance).The results showed that the concentration of spices had highly significant effect on ash content, fiber content and taste. The duration of storage gave highly significant effect on all parameters except on ash content and fiber. Interaction of the two factors had no significant effect on all parameters except taste. 60% spice and storage time of 8 day produced the best quality. Keywords: , cassava leaf, spices, storage time, Vegetables.